2006
DOI: 10.1242/dev.02305
|View full text |Cite
|
Sign up to set email alerts
|

A tyrosine-rich domain within homeodomain transcription factor Nkx2-5 is an essential element in the early cardiac transcriptional regulatory machinery

Abstract: Homeodomain factor Nkx2-5 is a central component of the transcription factor network that guides cardiac development; in humans, mutations in NKX2.5 lead to congenital heart disease (CHD). We have genetically defined a novel conserved tyrosine-rich domain (YRD) within Nkx2-5 that has co-evolved with its homeodomain. Mutation of the YRD did not affect DNA binding and only slightly diminished transcriptional activity of Nkx2-5 in a context-specific manner in vitro. However, the YRD was absolutely essential for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 58 publications
5
33
0
Order By: Relevance
“…After stage 20, SoNK4 ex-pression has been detected neither in branchial or systemic hearts nor gills. In a late stage of development (probably stage 26, personal communication), Elliott et al (2006) reported an expression of SoNK4 in the systemic heart but not in branchial hearts of Loligo paelii. These results confirm that expression of SoNK4 in gills and branchial hearts prospective areas is transient and restricted to the earlier stages of development in cephalopods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After stage 20, SoNK4 ex-pression has been detected neither in branchial or systemic hearts nor gills. In a late stage of development (probably stage 26, personal communication), Elliott et al (2006) reported an expression of SoNK4 in the systemic heart but not in branchial hearts of Loligo paelii. These results confirm that expression of SoNK4 in gills and branchial hearts prospective areas is transient and restricted to the earlier stages of development in cephalopods.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, NK4 is particularly interesting. This gene belongs to the NK gene cluster, which is probably the most ancient homeobox gene cluster, dating at least from the base of Metazoa (Larroux et al, 2007), and NK4 gene homologues have been identified in numerous species (Harvey, 1996;Elliott et al, 2006). Moreover, the main function of these genes seems to be highly conserved within Metazoa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence alignments demonstrate that the Ci-Nk4 homeodomain is highly conserved with those of vertebrate Nkx2 family genes (>90%). These alignments also indicate that Ci-Nk4 contains a N-terminal TN domain, linker and NK domains [42] along with a potential C-terminal tyrosine enriched domain or YRD [43]. Ci-Nk4 does not contain an Nkx2.5 box, but this domain is apparently specific to vertebrate orthologs (it is also not found in the Nkx2.5 ortholog from the invertebrate chordate, amphioxus, Amphi-Nk2Tin [26]).…”
Section: Nkx25/tinmanmentioning
confidence: 90%
“…More significantly, Ci-Nk4 lacks the highly conserved GIRAW domain that appears to mediate interaction with co-repressors in all other chordate Nkx2.5 orthologs. This domain is also absent in Drosophila tinman and other non-chordate orthologs [43].…”
Section: Nkx25/tinmanmentioning
confidence: 93%